2013
DOI: 10.1590/s1517-83822013005000049
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophytosis diagnosed at the Evandro Chagas Institute, Pará, Brazil

Abstract: Dermatophytosis is caused by a dermatophyte fungus that affects the stratum corneum and keratinized tissue. Dermatophyte fungus has been reported worldwide as the causative agent of dermatophytosis, but the etio-epidemiological aspects of these mycoses in the state of Pará remain unknown. The purpose of this study was to describe the etio-epidemiological profile of dermatophytosis diagnosed in patients at the Evandro Chagas Institute from May 2005 to June 2006. A total of 494 patients were admitted, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
(16 reference statements)
2
7
0
1
Order By: Relevance
“…Situação diversa da relatada na literatura, que cita Trichophyton equinum e Microsporum canis como os fungos que mais causam dermatofitose em equinos (Pereira et al 2006, Chermette et al 2008, Lyskova et al 2015. Uma importante implicação desse fato está na saúde pública, uma vez que o complexo T. mentagrophytes é uma espécie antropofílica muito mais comum e implicada em infecções humanas (Cafarchia et al 2013, Costa et al 1999, Silveira-Gomes et al 2013), enquanto T. equinum é zoofílico e raramente ocorre em humanos (Chabasse & Pihet 2008).…”
Section: Resultsunclassified
“…Situação diversa da relatada na literatura, que cita Trichophyton equinum e Microsporum canis como os fungos que mais causam dermatofitose em equinos (Pereira et al 2006, Chermette et al 2008, Lyskova et al 2015. Uma importante implicação desse fato está na saúde pública, uma vez que o complexo T. mentagrophytes é uma espécie antropofílica muito mais comum e implicada em infecções humanas (Cafarchia et al 2013, Costa et al 1999, Silveira-Gomes et al 2013), enquanto T. equinum é zoofílico e raramente ocorre em humanos (Chabasse & Pihet 2008).…”
Section: Resultsunclassified
“…Dermatophytosis is a fungal infection in keratinized tissues caused by dermatophytes. This mycosis exhibits a cosmopolitan profile and ranks among the most common infectious diseases that affect humans (Seebacher et al, 2008;Silveira-Gomes et al, 2013). Dermatophytes are specialized fungi in keratin degradation of infecting the stratum corneum, hair, claws, or nails.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of non-pigmented, septate hyphae in skin scales and ectothrix spores on hair surfaces observed by direct examination in this study agrees with the report of Silveira-Gomes et al . [25] who studied 494 human skin scrapings by direct examination and concluded that the presence of arthroconidia in skin scales is diagnostic of dermatophyte involvement.…”
Section: Discussionmentioning
confidence: 99%